1999
DOI: 10.1063/1.479291
|View full text |Cite
|
Sign up to set email alerts
|

Residual dipolar couplings by 1H dipolar-encoded longitudinal magnetization, double- and triple-quantum nuclear magnetic resonance in cross-linked elastomers

Abstract: The measurements of residual dipolar couplings in elastomer system is desirable, because they reflect the hindrance to molecular motions by the cross-linking, topological constraints and the external factors like mechanical stress. Dipolar-encoded longitudinal magnetization nuclear magnetic resonance (NMR) decay curves, double-quantum and triple-quantum NMR buildup intensities for measuring the residual dipolar couplings, and the associated dynamic order parameters are introduced. It is shown that in the short… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
197
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 99 publications
(199 citation statements)
references
References 32 publications
2
197
0
Order By: Relevance
“…Static 1 H Multiple Quantum NMR methods which measure the residual dipolar couplings, in specific, hold much promise for such efforts. [13][14][15][16][17][18][19][20]24 In elastomeric materials, the residual dipolar couplings have been shown to be the result of topological constraints interfering with fast reorientations on the NMR timescale that otherwise would be expected to average homonuclear dipolar couplings to zero. 9 The residual dipolar couplings, in fact, have been shown to be quite sensitive to network and morphological changes and have been used to test theories of polymer structure, ordering, and dynamics.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Static 1 H Multiple Quantum NMR methods which measure the residual dipolar couplings, in specific, hold much promise for such efforts. [13][14][15][16][17][18][19][20]24 In elastomeric materials, the residual dipolar couplings have been shown to be the result of topological constraints interfering with fast reorientations on the NMR timescale that otherwise would be expected to average homonuclear dipolar couplings to zero. 9 The residual dipolar couplings, in fact, have been shown to be quite sensitive to network and morphological changes and have been used to test theories of polymer structure, ordering, and dynamics.…”
mentioning
confidence: 99%
“…p. 4 More recently, it has been reported that the characterization of the growth of multiple quantum coherences can provide detailed insight into silicone network structure by increasing the selectivity of the NMR experiment to the structure and dynamics most connected to the topology of the polymer network, including chain ordering at the surface of inorganic filler particles. [13][14][15][16][17][18][19][20][21][22][23][24] In addition, it has been shown that echo based methods can over estimate the residual dipolar couplings due to the effects of magnetic susceptibilities and field gradients due to internal microscopic voids and the inorganic filler. 28 These effects have been observed to be large enough to reverse trends of <Ω d > vs crosslink density at different fields.…”
mentioning
confidence: 99%
See 3 more Smart Citations